Perancangan Metode Training Karyawan Harian Lepas di PT X - Marcel Marcel; Prayonne Adi (Jurnal Titra, 2022)
The problem that occurs at PT X is that HL employees have a low output when compared to permanent employees. This can be seen in the results of the Gauge R&R test where the error calue of all divisions is below 85%, where 85% is the company's standard regarding their understanding of how to inspect a product. With the error value that is below the company standard, it is necessary to find the root of the problem using the fishbone method. In determining the main factors causing HL employees to have low output, followed by the FMEA method, in order to see which factors are very influential in causing their low output. After the main factors are known, then proceed with the design of training methods that can solve the problems that occur. The new training method is a training method whose implementation is carried out for 8 days. The purpose of the 9 days training method is for employees to understand what materials they neef to master to become employees who have good productivity.